Finite element analysis of carbon fibre composite adaptive mirrors - Kendrew, S; Doel, P (2004)
With the advent of the new generation of ground-based telescopes with primary sizes of 30-100 m, adaptive optics (AO) technology is in rapid development. One important area of research is that of integration of AO into the telescope's operation. A possible solution for this is the use of an adaptive secondary mirror. However, for a secondary of several meters in size, this presents many problems in choice of material, as well as design for the adaptive control. An active mirror prototype made out of a carbon fibre composite material (CFC) is under development at University College London in collaboration with QinetiQ and Cobham Composites. We present here results from finite element analysis of this mirror, as well as modelling results of an adaptive secondary mirror section as might be developed for the new class of telescopes. These results indicate that CFC could indeed present a viable alternative to more traditional deformable mirror materials.